The role of sand filler in enhancing the mechanical properties of polymethylmethacrylate composites - Wolny, R.; Wiczenbach, T.; Pachocki, L.; Wilde, K.; Rucka, M. (Archives of Mechanics, 2025)
Polymethylmethacrylate (PMMA) is widely used in biomechanics and civil engineering for its properties. While various fillers have been studied to enhance mechanical properties of PMMA, the impact of sand as a filler has been less explored. This study investigates the effects of varying sand content on the mechanical properties and workability of PMMA-based resin composites, assessing their suitability for biomechanical applications. Specimen types with different sand contents (0%, 26%, 30%, and 52%) were examined through the cone spread test for workability, uniaxial tension tests for mechanical properties, and the finite element analysis (FEA) to simulate material behavior. Results were validated against numerical models to evaluate consistency. Adding sand significantly increased the Young modulus by 108%, 174%, and 286% for sand contents of 26%, 30%, and 52%, respectively, while decreasing the Poisson ratio. However, increased sand content reduced workability, highlighting a trade-off between mechanical strength and ease of handling. Numerical simulations, covering the sand volume ratio from 1% to 52% in 1% increments, showed that predictive accuracy varied: differences were up to 20%, for volume ratio up to 30%, while for contents above 30%, the discrepancies between model predictions and experimental data were below 5%. Incorporating sand into PMMA resin enhances its stiffness and suitability for biomechanical specimen testing. Sand-filled PMMA composites show promise for advanced engineering applications, though further optimization is needed to balance workability and mechanical strength.